Effects of lower fatigue protocols on motor neuron excitability in Korea National Team Taekwondo athletes - Kim, E.; Lim, S.-T.; Kim, K.; Lee, K.; Lee, B.; Kwak, T.; Jeon, M.; Kim, K.; Kim, D.; Park, J.; Song, J.-H. (Archives of Budo, 2019)
Background and Study Aim: Muscle fatigue and Golgi tendon organ laxity, which also, increases the threshold of muscle spindle discharge and disturbs afferent feedback. The purpose of this study was the effects of fatigue in lower extremities (quadriceps and hamstring) on H-reflex, M-wave, and Hmax/Mmax ratio changes in Korea National Team Taekwondo athletes.